1999
DOI: 10.1007/s002130051156
|View full text |Cite
|
Sign up to set email alerts
|

Serotonergic mediation of the effects of fluoxetine, but not desipramine, in the rat forced swimming test

Abstract: Depletion of serotonin prevented the behavioral effects of the selective serotonin reuptake inhibitor fluoxetine in the rat FST. Furthermore, depletion of serotonin had no impact on the behavioral effects induced by the selective norepinephrine reuptake inhibitor, desipramine. The effects of antidepressant drugs on FST-induced immobility may be exerted by distinguishable contributions from different neurotransmitter systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
137
1
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 339 publications
(162 citation statements)
references
References 25 publications
23
137
1
1
Order By: Relevance
“…Interestingly, it has been reported that a more than 90% depletion of cerebral 5-HT with the 5-HT synthesis inhibitor PCPA completely prevented the antidepressant action of fluoxetine in the forced swim test (Page et al, 1999). Clearly, the much more modest depletion of 5-HT produced in the present study with MDMA still allowed fluoxetine to have a marked behavioral effect in not only the forced swim test but also in other tests.…”
Section: Fluoxetine and Mdma Behavioral Effectsmentioning
confidence: 41%
See 1 more Smart Citation
“…Interestingly, it has been reported that a more than 90% depletion of cerebral 5-HT with the 5-HT synthesis inhibitor PCPA completely prevented the antidepressant action of fluoxetine in the forced swim test (Page et al, 1999). Clearly, the much more modest depletion of 5-HT produced in the present study with MDMA still allowed fluoxetine to have a marked behavioral effect in not only the forced swim test but also in other tests.…”
Section: Fluoxetine and Mdma Behavioral Effectsmentioning
confidence: 41%
“…Strain factors may also be a consideration: at least one recent study has failed to find an effect of chronic SSRI treatment on forced swim immobility in Wistar rats, despite clear effects being apparent in the Wistar-Kyoto strain (Tejani-Butt et al, 2003). Antidepressant effects in intact animals with fluoxetine have been frequently reported in the Sprague-Dawley strain (Detke et al, 1997;Detke and Lucki, 1996;Page et al, 1999), but infrequently, if ever, with Wistar strain rats. However, there is also at least one reported failure of chronic SSRIs to affect forced swim behavior in Sprague-Dawley rats at doses that clearly affected 5-HT turnover (Connor et al, 2000), suggesting that procedural factors in forced swim testing may also be important.…”
Section: Fluoxetine and Mdma Behavioral Effectsmentioning
confidence: 99%
“…Additional experiments in which 5-HT synthesis is blocked with p-cholophenylalanine (PCPA) can be performed to test this hypothesis. Involvement of 5-HT in the increased swimming activity was demonstrated by Page et al (1999) by blocking the synthesis of 5-HT with PCPA and suppressing the effects of 5-HT antidepressant drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Quantification of behaviors was performed by recording the predominant behavior in each 5 s period (Cryan and Lucki, 2000). We validated the scoring of the forced-swim test in our laboratory by treating additional normal control rats with desipramine (20 mg/kg subcutaneous) following standard procedures (Page et al, 1999). Results were similar to those reported previously: that is, increased climbing activity (17.872.7 counts vs 6.073.8 in saline treated animals) and decreased immobility (24.072.3 vs 38.376.6 in saline animals (Page et al, 1999).…”
Section: Forced-swim Testmentioning
confidence: 99%
“…Both SSRIs tested (ie fluoxetine and paroxetine), as well as the tricyclic, desipramine, the monoamine oxidase inhibitor, tranylcypromine, and the SNRI, nefazodone, dose-dependently decreased immobility in the FST indicative of an antidepressant-like effect. It is interesting to note that several of the antidepressant compounds tested were effective at reducing immobility in the gerbil FST at much lower doses as compared to those typically reported for mice and rats (Porsolt et al, 1977a, b;1978a, b;Page et al, 1999;Karolewicz and Paul, 2001;Bianchi et al, 2002;Crowley et al, 2004), although it is difficult to make direct comparisons because of the different routes of administration used in the present study (ie oral) vs many of the other studies (eg i.p.). Overall, these data are suggestive that the gerbil may be more sensitive species to psychoactive substances compared to mice and rats.…”
Section: Discussionmentioning
confidence: 55%